PENGARUH GAYA KEPEMIMPINAN, LOCUS OF CONTROL DAN KARAKTERISTIK INDIVIDU TERHADAP KEPUASAN KERJA ASN PADA KANTOR KECAMATAN TIROANG KABUPATEN PINRANG - Muhammad Kahar; Maryadi Maryadi; Muhammad Idris (Nobel Management Review, 2020)
The study aims to determine and analyze the influence of leadership style, locus of control, and individual characteristics individually and together on employee job satisfaction in Tiroang District Pinrang Regency. The design of this study uses survey research that takes samples from one population and uses questionnaires as a primary data collection tool. The study was conducted in the District of Tiroang Pinrang Regency. The time of the study was from October to November 2019. The population in the study were all employees of Tiroang Subdistrict, Pinrang Regency, amounting to 38 people. The sampling technique used in this study is census sampling or saturated sample, which is the total sample is all population. The number of samples in this study were 38 respondents. Data analysis using multiple regression analysis (multiple regression analysis) The results showed that there was an influence between leadership style, locus of control and individual characteristics individually and together on the job satisfaction of Tiroang District Pinrang District employees, as well as the variables of the most dominant individual characteristics influencing the job satisfaction of Tiroang District Pinrang District employee satisfaction.